The unfolded protein response (UPR) in cultured cells expressing either wild-type or mutant hepatitis B e antigen (HBeAG) of the hepaptitis B virus(HBV) - Bhoola, Nimisha Harshadrai (My University, 2014)
Hepatitis B virus (HBV) is hyperendemic to southern Africa, the Asia-Pacific region, and the Amazon Basin. HBV causes both acute, and chronic infection of the liver that result in a wide spectrum of liver diseases ranging from acute mild subclinical infection, and an asymptomatic carrier state (ASC) to severe clinical manifestations, including, severe acute and, chronic hepatitis, which can progress to cirrhosis, and the development of hepatocellular carcinoma (HCC). Several viral factors have been implicated in the activation, and inhibition of apoptosis. The development, and progression of this wide spectrum of liver diseases are associated with an unregulated increase or decrease in hepatocyte apoptosis as well as a loss of balance between cell proliferation, and apoptosis. In southern Africa, genotype A of HBV is the predominant genotype, with subgenotype A1 prevailing. Individuals infected with subgenotype A1 have several unique characteristics, including relatively lower levels of HBV DNA, and early seroconversion of hepatitis B e antigen (HBeAg) to antibodies against HBeAg during the course of HBV infection. Infection with this subgenotype is associated with rapid disease progression, and high frequency of HCC development. Moreover, patients infected with subgenotype A1 had increased levels of apoptosis when compared to the other subgenotypes. The G1862T mutation occurs most frequently in subgenotype A1. In the clinical setting, South African HCC patients infected with G1862T subgenotype A1 strains had higher levels of apoptosis while ASCs patients infected with G1862T subgenotype A1 strains had lower levels of apoptosis, when compared to those infected with wild-type. To date, G1862T has been functionally characterized in subgenotype A2, genotype B and in a genotype D HBV genome containing a subgenotype A1 precore (PreC) region. The objectives of our study were to construct 1.28 mer replication competent clones containing an endogenous HBV promoter for wild-type subgenotypes A1, A2, and D3 as well as mutant G1862T subgenotype A1, and to functionally characterize these strains in tissue culture. Transfection of Huh7 cells was used to follow the viral replication, expression of HBeAg, activation of the unfolded protein response (UPR), and subsequent apoptosis. The strategy used for the generation of these replication competent clones had several advantages. Very few PCR errors were introduced, and carry-over of enzymes, nonspecific products, and reaction reagents downstream was prevented. The clones contained endogenous HBV promoters, and enhancers, and were generated from a single complete genome of HBV. These replication competent clones may be used in future studies for the establishment of stable cell lines that constitutively express HBV proteins without the need for further manipulation. This strategy can be used for the generation of replication competent clones belonging to genotypes A to D, and G, and with a few minor modifications, for genotypes E, F, and H. Using the newly generated clones, their replication competence was demonstrated using transfection of Huh7 cells. Even in the absence of an exogenous promoter, these clones were able to support the expression of intracellular, and extracellular HBV DNA at levels of 108 to 109 genome copies/ml. HBcAg, HBeAg, and HBsAg were expressed for a period of five days, and the order of expression was similar to that seen during acute HBV infection. Comparison of transfection with a replication competent clone containing an exogenous HBV promoter demonstrated higher expression of HBV DNA, and proteins, as well as an earlier expression, and accumulation of HBeAg in the endoplasmic reticulum (ER) relative to the clone containing an endogenous HBV promoter. This initial increased accumulation of HBeAg in the ER did not affect the level of activation of the UPR, but led to an increased level of total cell death as a consequence of necrosis. When comparing the different subgenotypes following transfection into Huh7 cells, subgenotype D3 replicated at a lower level, as measured by HBsAg, and HBV DNA levels, with HBeAg passing through the secretory pathway earlier, when compared to cells transfected with genotype A. There was no difference in the intracellular, and extracellular HBsAg between cells transfected with either subgenotype A1 or A2. However, cells transfected with subgenotype A1 had higher levels of intracellular replicative intermediates, HBeAg, and HBcAg, and lower extracellular expression of HBeAg from days 1 to 3, when compared to cells transfected with subgenotype A2. The intracellular retention of the PreC/ core (C) precursor protein in cells transfected with subgenotype A1 was clearly demonstrated by its lower expression in the secretory pathway, and its higher co-localization in the nucleus, using indirect immunofluorescence. This intracellular retention led to greater ER stress, and an earlier, and prolonged activation of the UPR. This correlated well with the higher PERK, ATF6, and IRE1/XBP1 activity seen on days 3 than on day 5. These findings suggest that the prolonged activation of the UPR in cells transfected with subgenotype A1 led to increased apoptosis, and subsequent induction of liver damage, and may therefore, be a contributing factor to the higher hepatocarcinogenic potential of subgenotype A1. Our study demonstrated that G1862T reduced replication, and led to the initial temporal retardation of intracellular core-particle-associated HBV DNA. Although, G1862T did not affect HBsAg expression, it led to a decreased expression of HBcAg, and HBeAg. The decreased expression of extracellular HBeAg was probably as a result of decreased cleavage efficiency by the signal peptide, which consequently led to the retardation of the PreC/C precursor protein in the ER, and ER-Golgi intermediate compartment (ERGIC), and its decreased expression in the nucleus. This retardation, and accumulation led to the earlier activation of all three UPR pathways, but not to increased apoptosis. Therefore, it is evident that G1862T does not completely abolish HBeAg expression, but affects the rate of HBeAg maturation, and its expression through the secretory pathway. These findings suggest that in response to the accumulation of HBeAg in the ER, the UPR was activated resulting in the alteration of the capacity to overcome this stress, consequently leading to a new homeostasis of the ER being reached. The capacity of the ER is increased, with no further activation of the UPR and apoptosis, which facilitates maturation of HBeAg. In conclusion, our study for the first time demonstrated that there are a number of factors that influence the expression of proteins in HBV transfection studies including the type of transcriptional promoter, the different genotypes/subgenotypes of HBV, the use of protein expressing as opposed to replication competent clones, and the presence, and absence of mutations, such as the G1862T. Therefore, when comparing the outcomes of various experiments these factors should be taken into consideration, and the results interpreted with caution, because experiments may not be strictly speaking comparable. Importantly, replication competent clones were generated from strains circulating in southern Africa. The generation of these clones is an important step in further functional characterization of African strains of HBV, and their comparison to strains circulating other geographical regions of the world. These strains, in particular, subgenotype A1 can develop unique mutations, such as the G1862T, which we demonstrated can influence the expression of HBeAg, in a way that it can possibly account for the higher hepatocarcinogenic potential of subgenotype A1.
Keywords: Hepatitis B; Hepatitis Virus